Extensive Non-Coding Sequence Divergence Between the Major Human Pathogen Aspergillus fumigatus and its Relatives - Brown, Alec; Mead, Matthew E.; Steenwyk, Jacob L.; Goldman, Gustavo H.; Rokas, Antonis (Frontiers in Fungal Biology, 2022)
Invasive aspergillosis is a deadly fungal disease; more than 400,000 patients are infected worldwide each year and the mortality rate can be as high as 50-95%. Of the 450 species in the genus Aspergillus only a few are known to be clinically relevant, with the major pathogen Aspergillus fumigatus being responsible for 50% of all invasive mold infections. Genomic comparisons between A. fumigatus and other Aspergillus species have historically focused on protein-coding regions. However, most A. fumigatus genes, including those that modulate its virulence, are also present in other pathogenic and non-pathogenic closely related species. Our hypothesis is that differential gene regulation – mediated through the non-coding regions upstream of genes’ first codon – contributes to A. fumigatus pathogenicity. To begin testing this, we compared non-coding regions upstream of the first codon of single-copy orthologous genes from the two A. fumigatus reference strains Af293 and A1163 and eight closely related Aspergillus section Fumigati species. We found that these non-coding regions showed extensive sequence variation and lack of homology across species. By examining the evolutionary rates of both protein-coding and non-coding regions in a subset of orthologous genes with highly conserved non-coding regions across the phylogeny, we identified 418 genes, including 25 genes known to modulate A. fumigatus virulence, whose non-coding regions exhibit a different rate of evolution in A. fumigatus. Examination of sequence alignments of these non-coding regions revealed numerous instances of insertions, deletions, and other types of mutations of at least a few nucleotides in A. fumigatus compared to its close relatives. These results show that closely related Aspergillus species that vary greatly in their pathogenicity exhibit extensive non-coding sequence variation and identify numerous changes in non-coding regions of A. fumigatus genes known to contribute to virulence.